Silent Advanced Moyamoya Disease in an Asymptomatic Elderly Patient: A Rare Case Report - Putu Ayu Dyah Meita Wulandari; Shahifa Audy Rahima; I Gusti Agung Ayu Pramasinthya Aguseny Yudana; Yoanes Gondowardaja; Desie Yuliani (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2026)
Abstract Background: Moyamoya disease (MMD) is a rare cerebrovascular disorder characterized by progressive non-atherosclerotic steno-occlusion of the terminal portion of the internal carotid artery (ICA) and its major branches, leading to the formation of abnormal collateral vessels. The diagnosis of MMD is generally established based on the evaluation of neurological symptoms and brain imaging findings. However, asymptomatic MMD in elderly patients is rare and is often detected incidentally. Case Report: A 77-year-old man presented to the neurology outpatient clinic for a routine health evaluation. He had a history of hypertension and was compliant with regular antihypertensive medication, with no reported neurological symptoms. Neurological examination revealed no abnormalities. Brain magnetic resonance imaging (MRI) demonstrated occlusion of the M1 segment of the middle cerebral artery. Digital Subtraction Angiography (DSA) showed total occlusion of the left middle cerebral artery (M1 segment) with collateral circulation from the anterior cerebral artery, posterior cerebral artery, and superficial temporal artery, without delayed arterial filling, consistent with advanced-stage MMD (stage V–VI). The patient was managed conservatively with antiplatelet therapy, statins, and control of vascular risk factors. Discussion: The asymptomatic clinical presentation in advanced stages may be attributed to the development of adequate collateral circulation capable of maintaining cerebral perfusion. This hemodynamic compensatory mechanism may allow some patients to remain free of neurological deficits despite occlusion of major cerebral arteries. Conclusion: This case highlights that MMD can remain asymptomatic in elderly patients. Imaging modalities such as MRI and DSA play a crucial role in detecting occult cerebrovascular abnormalities and enabling appropriate monitoring and prevention of future cerebrovascular complications. Keywords: Moyamoya disease, cerebral collateral circulation, Digital Subtraction Angiography, silent cerebrovascular disease.